The influence of place and promotion in the omnichannel strategy framework on the purchase decision of Honda motorcycles at Daya Motor Soekarno Hatta Branch - Praja, Mochammad Firdaus Guntur Kusuma Ma; Bahri, Ronny Samsul (International Journal Labs, 2024)
This study explores the influence of place and promotion within the omnichannel strategy framework on the purchasing decisions of Honda motorcycles at Daya Motor's Soekarno Hatta branch. In Indonesia's competitive motorcycle industry, understanding consumer behavior and the factors influencing purchasing decisions is essential. Employing a quantitative survey method, data were collected through questionnaires distributed to Honda motorcycle consumers. The analysis reveals that both place and promotion significantly enhance consumer comfort and accessibility, with promotion particularly effective in attracting attention and building brand awareness. The integration of online and offline channels in an omnichannel strategy has been shown to improve consumer experiences and streamline decision-making processes. Additionally, the study finds that modern consumers increasingly rely on digital technology in their purchasing journeys, highlighting the need for dealers to adapt to these behavioral shifts. Daya Motor is advised to optimize its omnichannel strategy by enhancing service quality across all distribution channels and innovating promotional activities, thereby better meeting the diverse needs of discerning consumers. This research aims to provide valuable insights for Daya Motor's management to develop more effective marketing strategies that enhance sales and customer satisfaction.